Environmental NGOs involvement in dismantling illegal plastic recycling factory operations in Malaysia - Muhammad Shabir, Shaharudin; Fernando, Yudi; Ahmed, Essia Ries; Faizah, Shahudin (Universiti Malaysia Pahang, 2020)
The environmental issue is becoming an important sustainable development goal due to its devastating impact on the economy, society, and ecosystem. The need for managing environmental issues is leading a government to work closely with stakeholders such as environmental NGOs and local municipal councils. While collaboration between government and local municipal councils has been widely covered in the literature, the relationship between environmental NGOs and the government remains a complex issue. In the past, environmental NGOs have a responsibility to advise the government and create awareness to the public. However, the trend has soon changed, where environmental NGOs are becoming more active and influential in enacting policies to uphold environmental integrity. The purpose of this study is to investigate the role played by Malaysian environmental NGOs and the current states of environmental integrity in Malaysia. This study used a qualitative case study of illegal plastic recycling factories in Malaysia to achieve research objectives. The findings show that environmental NGOs in Malaysia are a mediator between the government and the public. However, environmental NGOs are now more active in influencing the public to pressure the government to uphold environmental integrity. In addition, Malaysia's environmental integrity has increased with several policies by the government for firms, and consumers are already in place and gearing towards zero plastics. An improvement from the government side should focus on an integrated waste management system to enables circular economy adoption among firms. This study novelty lies in the introduction of environmental NGOs as a mediator to foster Malaysian environmental integrity and integrated waste management